2017
DOI: 10.1155/2017/8948452
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Knowledge, Attitude, and Practice regarding Medical Nutrition Therapy in Patients with Diabetes: A National Cross-Sectional Study in Urban China

Abstract: To investigate the knowledge-attitude-practice (KAP) score in diabetes patients living in urban China regarding Medical Nutrition Therapy (MNT) and explore the influencing factors, this national survey recruited diabetes and prediabetes patients in 40 hospitals across 26 provinces in China. A self-designed questionnaire was used to collect the data and assess the knowledge, attitude, and practice regarding MNT. Logistic regression was used to explore the factor influencing KAP scores. A total of 6441 diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…The occupational status of T2DM patients influenced their dietary practices, which suggested that unemployed T2DM patients could undertake better dietary practice than employed T2DM patients. These data are in line with results from studies by Li and colleagues 6 and Asmelash and coworkers, 14 who found that KAP scores were significantly higher in retired patients than in those currently employed patients. This observation could be related to the fact that employed patients have careers to maintain, so their work and accompanying social activities restrict them from being concerned about their disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The occupational status of T2DM patients influenced their dietary practices, which suggested that unemployed T2DM patients could undertake better dietary practice than employed T2DM patients. These data are in line with results from studies by Li and colleagues 6 and Asmelash and coworkers, 14 who found that KAP scores were significantly higher in retired patients than in those currently employed patients. This observation could be related to the fact that employed patients have careers to maintain, so their work and accompanying social activities restrict them from being concerned about their disease.…”
Section: Discussionsupporting
confidence: 91%
“…These data are in line with studies showing an improved attitude and practice score with increasing knowledge scores. 6 , 7 , 34 , 35 The correlations among scores for KAP of T2DM patients and those of their FMs were pairwise significantly positive, demonstrating interactions between T2DM patients and FMs. 9 , 11 , 12 , 17 , 19 The dietary practice of FMs had a weaker positive correlation than dietary knowledge and attitude to the dietary practice of T2DM patients, which might be because FM’s behaviors are not always supportive and helpful.…”
Section: Discussionmentioning
confidence: 92%
“…This is because knowledge level is linked with panic emotion among most populations, which in turn influences their attitude and practices toward COVID-19 ( 18 ). The possible factors that could influence the knowledge, attitude, and practices include but not limited to sex, sources of information, and education level ( 17 , 19 ). Knowledge of the market vendors regarding COVID-19 and how they get information is a key measure in the fight against SARS CoV-2, however, a scarcity of epidemiological studies from rural communities in Africa created a rationale for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted before then also shows that female tend to have higher K and P scores but lower A scores, compared to the male patients. 16 …”
Section: Resultsmentioning
confidence: 99%